Analysis of the Implementation of Reasoning Learning Based on the Scientific Approach in Physics Learning - Effendy, Suhardi; Mudhofir, Faiz; Hartono, Hartono; Yulianti, Ian (Journal of Innovative Science Education, 2019)
Physics is an integral part of natural science. Basically physics is the study of natural phenomena in the form of facts, concepts and laws that have been tested by a series of studies. This study aims to describe the implementation of reasoning learning by teachers in public high school students in the city of Palembang. This type of research is descriptive qualitative research. The research was conducted in seven Palembang City State Senior High Schools on Momentum and Impulse material. Subjects in this study consisted of seven teachers and 231 students from seven public high schools in the city of Palembang. Research subjects were determined through purposive sampling technique. The results showed that the implementation of reasoning learning activities was not optimal. Learning the reasoning done by the teacher is limited to reasoning activities which is the final conclusion of the thinking process without observing, asking questions and trying. The final conclusions made by students are only based on the teacher's explanation of the one-way learning process. This can be seen from the percentage of the implementation of reasoning activities on the scientific approach that gets a percentage of 39.04% and is included in the medium category.